A Pediatric Case of Leptospirosis Developed after COVID-19 Associated Multisystem Inflammatory Syndrome - Kiana Razavi; Leila Shahbaznejad; Azin Hajialibeig; Mohammad Reza Navaeifar; Ali Sadeghi Lotfabadi; Mohammad Sadegh Rezai (Case Reports in Clinical Practice)
While presentations of novel severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) were observed to be mild in children, multi-system inflammatory syndrome in children (MIS-C) has emerged as one of the most critical phenomena in the era of Coronavirus disease 2019 (COVID-19). We present an eight-year-old boy with prolonged fever, weakness, myalgia, arthralgia, oliguria, hematuria, hemoptysis, and periumbilical pain. With regards to the history of contact with SARS-CoV-2 four weeks prior to symptom onset and prominent gastrointestinal symptoms, MIS-C was highly suspected. Furthermore, based on the compatible symptoms and history of white-water rafting and exposure to contaminated soil two weeks prior to admission, leptospirosis was probable. Of note, Leptospirosis immunoglobulin M and COVID-19 immunoglobulin G were detectable. Lifesaving supportive measures, empirical antibiotic therapy, Remdesivir, Dexamethasone, and Prednisolone pulse therapy were prescribed. Afterward, gradual clinical improvement was shown. We aimed to report a case with MIS-C accompanied by severe leptospirosis to emphasize that in endemic areas of leptospirosis, considering the co-occurrence of MIS-C and other inflammatory disorders is crucial for multidisciplinary management.